PENERAPAN APLIKASI MICROSOFT TEAMS PADA PEMBELAJARAN DARING PENDIDIKAN AGAMA ISLAM KELAS VII BRAWIJAYA SMART SCHOOL MALANG PADA MASA PANDEMI CPVID19 - Yunara Maufiroh; Mohammad Afifulloh; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This article aims to apply The Microsoft Teams application in online learning of Islamic Religious Education class VII Brawijaya Smart School Malang. Data from this study was obtained from observations, interviews and documentation. The results of this study show that the application of Microsoft Teams facing the implementation of online learning, the application can be one of the learning process applications for teachers and students, and facilitate students in meetings, material delivery, and assignments until the collection of assignments. As for teachers also facilitate in the delivery of materials to students.supporting factors and inhibitions of the application students do not donate too much application because the application is enough to facilitate teachers and students, and obstacles for students that is kuranya support from parents to learning during home. This shows that the use of applications in online learning is very important for learners.Kata Kunci: Microsoft Teams, Online Learning, PAI Learning